A Modified Anchor Free Localization Technique for Wireless Sensor Network - Kumar Shah, Indra; Singh Dohare, Yogendra; Singh Yadav, Dharmendra (EAI Endorsed Transactions on Cloud Systems, 2020)
INTRODUCTION: A novel anchor-free localization technique for a single-hop wireless sensor network is proposed, which is based on internode distances only. The average of the internode distances is mainly used to localize the reference node in the proposed algorithm. Average localization error is used as the main performance metric. The simulation result shows that the proposed algorithm significantly reduces localization error as compared with conventional localization techniques with respect to node density variation and network size. OBJECTIVES: To find the location of the randomly deployed sensor nodes. METHODS: An anchor free localization method is used to find the location of the deployed sensor nodes. RESULTS: Location error is comparatively less in the proposed strategy. CONCLUSION: For single-hop wireless sensor networks using inters node distance, a novel anchor free localization technique is presented.